2020
DOI: 10.1111/evj.13222
|View full text |Cite
|
Sign up to set email alerts
|

Single and repeated intra‐articular injections in the tarsocrural joint with allogeneic and autologous equine bone marrow‐derived mesenchymal stem cells are safe, but did not reduce acute inflammation in an experimental interleukin‐1β model of synovitis

Abstract: Background Allogeneic and autologous bone marrow‐derived mesenchymal stem cells (BMDMSCs) have been administered in equine joints for their anti‐inflammatory effects. However, allogeneic BMDMSC offer multiple clinical and practical advantages. Therefore, it is important to determine the relative effectiveness of allogeneic vs autologous BMDMSCs. Objectives The objective of the study was to compare the inflamed joint response to autologous vs allogeneic BMDMSCs injections, and to determine if either treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…A study using a chemically induced-model of arthritis in the horse showed significant upregulation of type 2 collagen and significantly decreased expression of inflammatory mediators in cartilage at 6 months post-treatment when allogeneic MSC-treated joints were compared to untreated joints, though no significant gross nor histologic improvement was seen (Table 2) (33). In a similar study, allogeneic MSCs did not cause significant clinical improvement in IL-1beta-induced arthritis, however, this was a very acute and severe inflammatory model (Table 2) (97). Additional allogeneic MSC studies focusing on joint disease in the horse have shown beneficial clinical and histologic results using blood-derived (81), neonatal-derived (82), or adiposederived MSCs (Table 2) (83).…”
Section: Results Of Allogeneic Msc Therapy For Musculoskeletal Diseasementioning
confidence: 96%
“…A study using a chemically induced-model of arthritis in the horse showed significant upregulation of type 2 collagen and significantly decreased expression of inflammatory mediators in cartilage at 6 months post-treatment when allogeneic MSC-treated joints were compared to untreated joints, though no significant gross nor histologic improvement was seen (Table 2) (33). In a similar study, allogeneic MSCs did not cause significant clinical improvement in IL-1beta-induced arthritis, however, this was a very acute and severe inflammatory model (Table 2) (97). Additional allogeneic MSC studies focusing on joint disease in the horse have shown beneficial clinical and histologic results using blood-derived (81), neonatal-derived (82), or adiposederived MSCs (Table 2) (83).…”
Section: Results Of Allogeneic Msc Therapy For Musculoskeletal Diseasementioning
confidence: 96%
“…We show that recipient anti-bovine titers cause antibody mediated death of MSCs that have been prepared with FBS, with resultant local inflammation and reduced synovial MSCs after intra-articular administration. The historic and current use of FBS for MSC preparation is likely to misrepresent MSC effect because of cytotoxicity and adverse responses to MSCs with FBS contamination ( 10 , 42 , 49 ). When evaluating reported pre-clinical, veterinary, and human clinical trials, the use of FBS should be considered when interpreting results ( 4 , 9 , 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of FBS is decreasing because of ethical concerns, availability, and the risk of disease transmission from bovine products (7). Despite this shift in FBS acceptance, FBS supplemented MSCs have market approval for use in humans in Canada and New Zealand, and FBS supplementation remains the industry standard in pre-clinical and veterinary MSC use (4,5,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Adult articular cartilage has very limited ability for self-repair and current treatment strategies, such as NSAIDs and intra-articular injections with corticosteroids, are only palliative in nature and have little impact on the progressive degeneration of articular cartilage [ 152 , 153 , 154 , 155 , 156 ]. Consequently, there is a large unmet need for efficacious disease-modifying therapies, and thus a growing interest in regenerative medicine approaches.…”
Section: Regenerative Therapies By Disease Areamentioning
confidence: 99%
“…To further improve the effect of MSC therapies proinflammatory or chondrogenic priming strategies for MSC prior to injection were tested, the latter of which was proven to be safe although differentiation of equine bmMSCs may increase the expression of immunogenic proteins [ 31 , 168 , 169 ]. Additionally, the intra-articular administration of allogeneic and even xenogeneic MSCS for the treatment of OA has been tested in multiple clinical studies in horses with equivocal results [ 156 , 170 , 171 ]. Although some studies show an immune reaction to allogeneic and xenogeneic stem cells [ 172 ], the immune response in vivo seems to be mild, and allogeneic MSCs application has been reported to be safe for intra-articular use in equine patients [ 173 , 174 , 175 , 176 ].…”
Section: Regenerative Therapies By Disease Areamentioning
confidence: 99%